2023
DOI: 10.1371/journal.pone.0290145
|View full text |Cite
|
Sign up to set email alerts
|

True mineral digestibility in C57Bl/6J mice

Abstract: Data on mineral digestibility is key to understand mineral homeostasis and refine the recommendations for the dietary intake of these nutrients. In farm animals and pets, there is plenty of data on mineral digestibility and influencing factors. In laboratory mice, however, there is a lack of information on mineral digestibility under maintenance conditions, although this should be the basis for studies on mineral homeostasis under experimental conditions. The aim of the present study was to analyse data on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…The apparent phosphorus digestibility of both mouse lines in this study was slightly higher than that found previously in C57Bl/6 J strain 20 . Phosphorus intake and apparently digested amount of phosphorus were correlated linearly (R 2 = 0.88) and the mean true phosphorus digestibility amounted to 81%.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…The apparent phosphorus digestibility of both mouse lines in this study was slightly higher than that found previously in C57Bl/6 J strain 20 . Phosphorus intake and apparently digested amount of phosphorus were correlated linearly (R 2 = 0.88) and the mean true phosphorus digestibility amounted to 81%.…”
Section: Discussioncontrasting
confidence: 80%
“…This difference might be due to the different natural type of diet (herbi-omnivorous vs. herbivorous), but can only be speculated upon in this study. The Lucas-test for calcium in the mice showed sufficient linearity (R 2 = 0.73) and the resulting mean true digestibility of 65% is much higher than the value of 33% found in C57Bl/6 J mice in four diet groups in a previous study 20 . The feed intake per mouse per day was considerably lower in the present study, which may have a positive influence on calcium absorption via faecal DM excretion.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations